Change in Alcohol Consumption and Physical Activity During COVID-19 Pandemic Amongst 76 Medical Students - Sandell, Christina (My University, 2025)
Objective: To investigate whether the COVID-19 pandemic has affected physical activity and alcohol consumption among medical students. Methods: Cross-sectional survey study among 76 students in their second year of medical school. The Wilcoxon sign-rank test and Kruskal-Wallis H test were used to assess the difference between groups. Results: Of 76 respondents, 68% were women, 66% were single and 34% were co-habiting. The median age was 21 years. Overall alcohol consumption decreased during the pandemic year by 12 g/week. Overall physical activity did not significantly change. The decrease in alcohol consumption was mostly caused by a change seen in a high tertile, change was -96 g/week. Alcohol consumption decreased more in women than in men, p=0.0001. Conclusions: It seems that alcohol consumption among medical students has decreased during the COVID-19 pandemic probably due to reduced social contacts and negative effect of social isolation. This decrease was seen especially among women and among students with higher alcohol consumption before the pandemic. Also, it seems that students had found their ways to remain active during the pandemic since the amount of leisure-time physical activity had not changed significantly.

Tutkimuksen tarkoitus: Selvittää, onko COVID-19-pandemia vaikuttanut lääketieteen opiskelijoiden liikunnan määrään ja alkoholinkäyttöön. Käytetyt tutkimusmenetelmät: Kyselyn avulla toteutettu poikittaistutkimus, johon osallistui 76 toisen vuoden lääketieteen opiskelijaa. Wilcoxon merkittyjen sijalukujen testiä ja Kruskal-Wallis H -testiä käytettiin ryhmien välisten erojen määrittämiseen. Tutkimustulokset: 76:sta vastaajasta 68 % oli naisia, 66 % yksinasuvia ja 34 % asui yhdessä jonkun kanssa. Mediaani-ikä oli 21 vuotta. Kokonaisuudessaan alkoholinkäyttö väheni 12 g /viikko pandemiavuoden aikana. Liikunnan määrä ei merkittävästi muuttunut. Alkoholinkäytön väheneminen johtui suurelta osalta muutoksesta ylimmässä tertiilissä, jossa muutos oli -96 g/viikko. Alkoholinkäyttö väheni enemmän naisilla kuin miehillä, p=0,0001. Päätelmät: Vaikuttaa siltä, että lääketieteen opiskelijoiden alkoholinkäyttö on vähentynyt COVID-19-pandemian aikana mahdollisesti johtuen sosiaalisten kontaktien vähenemisestä. Tämä muutos näkyi erityisesti naisten ja ennen pandemiaa enemmän alkoholia käyttävien keskuudessa. Vaikuttaa myös siltä, että opiskelijat olivat löytäneet keinoja pysyä aktiivisena pandemian aikana, sillä vapaa-ajan liikunnan määrä ei merkittävästi muuttunut.
Keywords: covid-19, alcohol, physical activity, modifiable risks